Existence of Solutions for Generalized Nonlinear Fourth-Order Differential Equations - Salah Benhiouna; Azzeddine Bellour; Reemah Alhuzally; Ahmad M. Alghamdi (Mathematics)
In this article, we studied the existence of solutions for a more general form of nonlinear fourth-order differential equations by using a new generalization of the Arzelá–Ascoli theorem and Schauder fixed theorem under easier and general conditions. Moreover, we provided some sufficient conditions on the nonlinear function that allowed us to deduce the nonexistence results. Finally, we outlined an example to illustrate our main results.